2018
DOI: 10.3390/life8040059
|View full text |Cite
|
Sign up to set email alerts
|

How do Nucleotides Adsorb Onto Clays?

Abstract: Adsorption of prebiotic building blocks is proposed to have played a role in the emergence of life on Earth. The experimental and theoretical study of this phenomenon should be guided by our knowledge of the geochemistry of the habitable early Earth environments, which could have spanned a large range of settings. Adsorption being an interfacial phenomenon, experiments can be built around the minerals that probably exhibited the largest specific surface areas and were the most abundant, i.e., phyllosilicates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 93 publications
1
26
0
Order By: Relevance
“…This is consistent with the idea suggested by Clark and Kolb [46] who discussed the possibility of various stages from abiotic synthesis to the possible origin of life to have happened in separate ponds or other sites that might be interconnected, and thus various multi-pot processes could potentially be mixed [47][48][49][50]. Hence, the GP produced under hot conditions was transferred to the water bodies with lower temperatures fairly quickly [46,[51][52][53][54] where it could then become incorporated into other prebiotic processes.…”
Section: Resultssupporting
confidence: 87%
“…This is consistent with the idea suggested by Clark and Kolb [46] who discussed the possibility of various stages from abiotic synthesis to the possible origin of life to have happened in separate ponds or other sites that might be interconnected, and thus various multi-pot processes could potentially be mixed [47][48][49][50]. Hence, the GP produced under hot conditions was transferred to the water bodies with lower temperatures fairly quickly [46,[51][52][53][54] where it could then become incorporated into other prebiotic processes.…”
Section: Resultssupporting
confidence: 87%
“…In addition, both the properties of the eDNAss molecules and those of the studied soil (Table 1) further provide a plausible explanation of the obtained results [28]. First, the detected dominance of Mg 2+ and Ca 2+ cations in the soil solution (Table 1) have limited the interaction of the phosphate groups (strong) of eDNAds and eDNAss with the -O(H), -Si, -Al, -Fe sites of the soil minerals [29,19], and stimulated their electrostatic interactions (weak) [30,31]. Furthermore, the small molecular size of eDNAss (S1B Fig) has favored its adsorption in high amounts but also limited the binding sites per molecule, thus, facilitating its high desorption as evidenced by the high amounts of both wa and ta fractions (Fig 2) [32].…”
Section: Discussionmentioning
confidence: 79%
“…The soil in the mesh bags, as well as the soil in which the bags were buried, are both classified as silty clay loams (Natural Resources Conservation Service, 2017), with a 27–40% clay content. It has been shown that DNA molecules can interact with negatively charged clay particles (Pedreira‐Segade et al, 2018), forming stabilized DNA/clay complexes. DNA stabilization is conferred both by the resistance of the complexed DNA molecule to enzymatic processes (Crecchio & Stotzky, 1998), and the immobilization of DNases, which also form complexes with clay particles (Demanèche et al, 2001).…”
Section: Discussionmentioning
confidence: 99%